Options for Child Benefits in Kosovo : Synthesis of International Experiences and Considerations for Kosovo in Response to Parliament Resolution on Child Allowances - Brodmann, Stefanie; Gotcheva, Boryana; Kerschbaumer, Florentin; Elezaj, Erëblina (World Bank, Washington, DC, 2019)
Kosovo is the second poorest country in Europe, after Moldova, with one in five Kosovars living in poverty. Improved economic conditions in the country have yet to translate into significant poverty reduction. The poor are over-represented in households headed by women, in households in which the head has not completed secondary education, in households with more children, in larger households, and among people whose main source of income is social assistance, specifically category I social assistance scheme beneficiaries. Child benefits are one of the most common components of the family benefit systems in the European countries, and worldwide. They are part of a broader set of measures aimed at reducing poverty and vulnerability of families with children. The Social Assistance Scheme is Kosovo’s overarching program for protection against poverty of various vulnerable groups. Beneficiary families of the social assistance scheme receive a child supplement for each child. On November 7, 2018, the Parliament of the Kosovo adopted a resolution calling on the government of Kosovo to draft legislation for a state budget financed child benefit, considering criteria such as family income, employment status of parents, and children’s age. This note provides an overview of international experiences with child benefits and uses data from the Kosovo household budget survey to assess the impact of various options for protecting children against poverty. To avoid duplicating the existing child supplement, the targeting mechanism and implementation rules for any new child benefit should, at the very least, be coordinated with the targeting design and implementation arrangements of the social assistance scheme.